Role of Biogenic Capping Agents in the Synthesis of Metallic Nanoparticles and Evaluation of Their Therapeutic Potential - Sidhu, Amanpreet K.; Verma, Naveen; Kaushal, Priya (Frontiers in Nanotechnology, 2022)
The biomedical properties of nanoparticles have been the area of focus for the contemporary science; however, nonetheless there are issues concerning their long-term toxicities. Recent trends in nanoparticle fabrication and surface manipulation, the use of distinctive biogenic capping agents, have allowed the preparation of non-toxic, surface functionalized and monodisperse nanoparticles for the medical applications. These capping agents act as stabilizers or binding molecules that prevent agglomeration and steric hindrance, alters the biological activity, surface chemistry and stabilizes the interaction of nanoparticles within the preparation medium. Explicit features of nanoparticles are majorly ascribed to the capping present on their surface. The present review article is an attempt to compile distinctive biological capping agents deployed in the synthesis of metal nanoparticles along with the medical applications of these capped nanoparticles. Firstly, this innovative review highlights the various biogenic capping agents including biomolecules and biological extracts of plants and microorganisms. Next, the therapeutic applications of capped nanoparticles and the effect of biomolecules on the efficiency of the nanoparticles have been expounded. Finally, challenges and future directions on the use of biological capping agents have been concluded. The goal of the present review article is to provide a comprehensive report to researchers who are looking for biological alternatives for the green synthesis of important metallic nanoparticles.